Analysis of Processing Empty Oil Palm Fruit Bunch Waste (EFB) Into Organic Fertilizer and Organic Mulch - Qiswatun Mukhoyyaroh; Latif Sofiana Nugraheni; Ina Rotul Mila; Risa Maelani; Indah Anugrah Sari (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kuningan, 2025)
Fresh fruit bunches (FFB) of oil palm are processed into crude palm oil (CPO) and palm oil waste. Palm oil waste, such as empty fruit bunches (EFB), has traditionally been incinerated, leading to increased carbon emissions in the atmosphere. However, EFB can be utilized as organic fertilizer and mulch for oil palm cultivation. This study aims to analyze the conversion of EFB waste into organic fertilizer and mulch. The research was conducted at PT Perkebunan Nusantara VII Kertajaya, Banten Province, from July 2023 to August 2024. A qualitative descriptive approach was employed, with data collected through observation, interviews, and documentation. Participants were selected using purposive sampling, involving 20 individuals. The results indicate that the process of converting EFB waste into organic fertilizer and mulch comprises two main stages: (1) the processing of FFB into EFB waste, which includes the following steps: a) weighing, b) sorting, c) loading ramp, d) sterilization, e) stripping, and f) empty bunch hopper; and (2) the transformation of EFB waste into organic fertilizer and mulch. The production process for organic fertilizer and mulch occurs naturally. The EFB waste is applied as organic fertilizer and mulch by spreading it on the soil around the oil palm trees.